Barry Lyndon [videorecording (DVD)] - Kubrick, Stanley; O'Neal, Ryan; Berenson, Marisa, 1942-; Magee, Patrick; Krüger, Hardy, 1928-; Körner, Diana, 1944-; Hordern, Michael, 1911-1995; Thackeray, William Makepeace, 1811-1863 (Distributed by Warner Home Video, 2007)
Rise and fall of a young 18th century Irishman bent on achieving fame and fortune, mainly by marriage.